KRITIK SOSIAL MODEL PUISI MASKUMAMBANG KARYA W.S. RENDRA (KAJIAN SOSIOLOGI SASTRA ALAN SWINGEWOD) - lailiyatur_ rohmah95 (ESTETIKA: JURNAL PENDIDIKAN BAHASA DAN SASTRA INDONESIA, 2022)
Masumambang poem by W.S. Rendra illustrates the character Aku who responds or responds to the various obstacles faced both from inside and outside himself, namely society, government and the nation. Indirectly, this poem can function as a socio-cultural document and a reflection of society. This research seeks to see literary works as a mirror and social reality. The method used in this research was through understanding the text and literature study, and then the social analysis was carried out using Alan Swingewood's sociological analysis knife. The problem of this research lies in the text and its relationship with the community. The purpose of this study is to determine the structure of the text in order to find the meaning of poetry and its relationship with the context of dialectical society and to find the world view of the poet Alan Swingewood classification as a mediation between text and society. The results of the research in this article show that there are two perspectives, the first is the social facts of the character Aku, who expresses a lot of sadness seeing the welfare of his nation and hopes to be free from colonialism, the second is the description of the structure of Masumambang poetry and social criticism of the Masumambang poetry model of the facts of humanity, love, and patriotism. , and a world view of the society that surrounds it. Keywords: Maskumambang poetry, W.S. Rendra, Sociology of Literature, Alan Swingewood.